Biometric System Based Electronic Voting Machine - T. Haripriya; Vinodkumar B G; Mahesh Babu; G. Aswini; Rekha M S (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Through voter identity verification, the avoidance of duplicate voting, and the reduction of problems like ballot rigging and voter impersonation, biometric authentication—more specifically, fingerprint scanning—improves voting security and accuracy. Before enabling voters to cast their ballots, the proposed biometric Electronic Voting Machines (EVMs) use fingerprint sensors combined with microcontrollers such as ARM9. In addition to displaying voter data, such as name, photo, constituency, and ID, following authentication for transparency, these EVMs provide instantaneous transfer of voting results to a central server for oversight. Compared to conventional paper-based or electronic systems, biometric-based EVMs are intended to improve voting process security, efficiency, and integrity.